2019
DOI: 10.3390/brainsci9120337
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Retinal OCT and Their Correlations with Neurological Disability in Early ALS Patients, a Follow-Up Study

Abstract: Background: To compare early visual changes in amyotrophic lateral sclerosis (ALS) patients with healthy controls in a baseline exploration, to follow-up the patients after 6 months, and to correlate these visual changes with neurological disability. Methods: All patients underwent a comprehensive neurological and ophthalmological examination. A linear mixed analysis and Bonferroni p-value correction were performed, testing four comparisons as follows: Control baseline vs. control follow-up, control baseline v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 67 publications
7
41
1
1
Order By: Relevance
“…Several studies have found a positive correlation between retinal thinning and ALS patients (Hubers et al, 2016;Mukherjee et al, 2017;Rojas et al, 2019). However, loose connections may be made regarding ALS and rhodopsin, as one study has found a correlation between ER stress and ALS pathogenesis (Webster et al, 2017).…”
Section: Rhodopsin and Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Several studies have found a positive correlation between retinal thinning and ALS patients (Hubers et al, 2016;Mukherjee et al, 2017;Rojas et al, 2019). However, loose connections may be made regarding ALS and rhodopsin, as one study has found a correlation between ER stress and ALS pathogenesis (Webster et al, 2017).…”
Section: Rhodopsin and Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…While one study did not demonstrate a correlation between RNFL thickness and the ALSFRS-R score and their progression rates (Mukherjee et al, 2017), other authors found a correlation with some OCT parameters (Abdelhak et al, 2018;Liu et al, 2018;Rohani et al, 2018;Rojas et al, 2019;Salobrar-García et al, 2019). In a study of the pRNFL thickness in four quadrants, the average pRNFL thickness showed a significant positive correlation with the ALSFRS-R score (Rohani et al, 2018), and the pRNFL thickness in the inferior sector was negative (Rojas et al, 2019). When the analysis was more detailed, dividing the papilla into 12 hourly sectors, sectors H5 and H6 had a positive direct significant correlation, and H8 had an inverse significant correlation of pRNFL with the ALSFRS-R values (Rojas et al, 2019).…”
Section: Optical Coherence Tomographymentioning
confidence: 89%
“…Using SD-OCT, the authors observed that (i) in ALS patients compared with the controls, there was a decrease in total macular volume; (ii) 37.5% of ALS patients showed an average pRNFL below the first percentile, and temporal and papillomacular bundle were more affected; and (iii) in ALS patients, the total macular thickness and pRNFL thickness correlated inversely with the time of evolution of ALS (Volpe et al, 2015). Recently, in a study performed in early ALS patients with spinal onset and without ocular diseases, a significant macular thickness increase was found in the temporal and inferior areas of the inner macular ring in comparison with that in a healthy control, suggesting that this retinal thickening in early ALS patients could be due a microglial activation in the neuroinflammatory process (Ringelstein et al, 2014;Rojas et al, 2019). In contrast, in another study in ALS patients, only the macular retinal nerve fiber layer (mRNFL) showed a significant thickness decrease by OCT, which correlated positively with pulmonary function tests (Simonett et al, 2016).…”
Section: Optical Coherence Tomographymentioning
confidence: 97%
See 2 more Smart Citations